Optical fiber sensors for loT and smart devices - Domingues, Maria de Fátima F.; Radwan, Ayman, 1976- (Springer, 2017)
This brief provides a review of the evolution of optical fiber sensing solutions and related applications. Unique production methods are presented and discussed, highlighting their evolution and analyzing their complexity. Under this scope, this brief presents the existing silica optical fiber sensors and polymer optical fiber sensors solutions, comparing its field of action (sensitivity, accuracy), complexity of manufacture and economic cost. Special attention is given to low-cost production methods. This brief evaluates the different existing techniques, assessing the accuracy and suitability of these sensors for possible Internet of Things (IoT) integration in different considered scenarios. Critical analytical techniques, also covered in this brief, are expected to play a key role in the world of IoT and the smart city of tomorrow.
Keywords: Internet of things.; Intelligent sensors.; Wireless communication systems.; elektronické knihy; electronic books